Phase 3 randomized study for evaluation of physician choice Rx versus best supportive care as second-line or beyond therapy in head and neck cancer with poor performance status - Patil, Vijay Maruti; Bhosale, Bharatsinha Baburao; Noronha, Vanita; Prabhash, Kumar (Journal of clinical oncology, 2024)
LBA6019Background: Relapsed-recurrent head and neck squamous cell carcinoma (HNSCC) cancers have limited treatment options in the second line and beyond setting. Many of these patients have poor performance status (PS) and are subject to best supportive care (BSC). There is a lack of any level 1 evidence about the benefit of systemic therapy in HNSCC with poor PS. Methods: This was a randomized phase 3 superiority open-label multicentric study. Adult patients (age>=18 years) with relapsed-recurrent HNSCC, qualified to receive 2nd line or beyond systemic palliative therapy and had ECOG PS 2-3 were eligible. Such patients underwent central stratified random assignment 2:1 to either physician choice therapy either triple metronomic chemotherapy (tablet erlotinib 150 mg [fixed-dose] OD, capsule celecoxib 200 mg [fixed-dose] BD, and oral weekly methotrexate 9 mg/m2 orally or intravenous docetaxel [75 mg/m2 3 weekly]) or BSC. The chemotherapy was continued either till the progression of the disease or till the development of intolerable side effects. The primary endpoint was 6 month-overall survival (OS). The OS in the 2 arms was estimated using the Kaplan-Meier method and by log-rank test. A p-value of 0.05 was considered significant. Sample size: The 6-month OS assumed based on our previous data was 20%, we had assumed that it would increase to 50% in the intervention arm with a type 1 error of 5%, type 2 error of 20%, 2:1 allocation (1- BSC and 2- intervention) and 10% lost to follow up rate. The sample size required was 66. The events required for analysis were 47. Results: The study recruited 66 patients between 1st September 2022 to 27th December 2022 with 44 patients in physician choice therapy (PCT) and 22 in the BSC arm. The data was censored for analysis on 1st March 2024. The median age was 50 years (Range 25-75) with a predominantly male population (n=53;85%). The ECOG PS was PS 2 in 56 (84.8%) and PS 3 in 10 (15.2%) patients. The predominant site of primary was the oral cavity with 52 patients (78.8%). The previous number of systemic lines of therapy received were 1 in 41 (62.1%), 2 in 22 (33.3%), and >2 in 3 (4.5%) patients. Except for 2, all patients had a platinum refractory status (64;97%). The PCT was triple metronomic chemotherapy in 41 patients (93.2%; n=44) and docetaxel in 3 patients (6.8%; n=44). The 6-month OS was 9.09% (95% CI 1.56-25.1) in the BSC versus 53.8% (95% CI 37.9-67.2) in the PCT arm (P<0.0001). The median overall survival in PCT was 223.0 days (95% CI 129-283) versus 77.5 days (95%CI 58 -110) in the BSC arm. The corresponding hazard ratio was 0.333 (95%CI 0.187-0.593; P<0.0001). The data regarding adverse events will be presented at the conference. Conclusions: In this first-ever randomized study on poor PS HNSCC patients, warranting second-line and beyond therapy, the administration of systemic therapy led to a substantial improvement in OS. Clinical trial information: CTRI/2022/08/044733.